2020
DOI: 10.1021/acs.jpcc.9b11821
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Dependence in Photothermal Heating of Gold Nanomaterials with Near-Infrared Laser

Abstract: The selection of gold nanomaterials (GNMs) for potential use in photothermal therapeutic applications depends on a few parameters including their morphology, size, and surface functionalization. We report experimental and theoretical studies of the photothermal efficiency of GNMs of a few different morphologies, including gold nanoparticles (AuNPs) of the spherical shape, gold nanorods (GNRs), and gold nanourchins (GNUs), as well as spherical gold nanoparticle conjugates (AuNPC), where 20 nm AuNPs were functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Recently, we investigated a set of nano-gold with different morphologies such as GNSs, GNRs, GNUs, and gold conjugates with IR dye attached to 20-nm GNSs. We found that AuNPC exhibit an enhanced ‘light to heat energy conversion efficiency (η)’ by a factor four than those in the unmodified gold nanospheres 19 .…”
Section: Introductionmentioning
confidence: 86%
“…Recently, we investigated a set of nano-gold with different morphologies such as GNSs, GNRs, GNUs, and gold conjugates with IR dye attached to 20-nm GNSs. We found that AuNPC exhibit an enhanced ‘light to heat energy conversion efficiency (η)’ by a factor four than those in the unmodified gold nanospheres 19 .…”
Section: Introductionmentioning
confidence: 86%
“…36 This further proves that the coupling effect brought by the gap between the particles can enhance its photothermal performance. Most of the existing studies focused on the photothermal performances of AuNPs dispersions and nanoparticle array patterned on at surfaces, [37][38][39][40][41] but few reported the heat generation capability of the gold nanoparticle arrays on the surface of other nanospheres for their potential photothermal application. 42 For multi-component core-shell gold nanomaterials, more attention has been paid on the photothermal conversion capability of the gold shell.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature elevation is more important in the case of GNR than GNU at the same concentration as already reported in other similar works. [51] The temperature elevation ΔT after 15 min versus concentration is reported in Figure 3. ΔT increases linearly with nanoparticles concentration and is highly dependent on the illumination wavelength compared to the LSPR position.…”
Section: Gnrs Heating Measurements Under Near-ir Illuminationmentioning
confidence: 99%
“…This phenomenon was recently demonstrated by Alrahili at al. [51] since GNRs absorb more light and quickly convert it to heat especially when the absorption matches with the laser wavelength. www.advancedsciencenews.com www.particle-journal.com…”
Section: Gnrs Heating Measurements Under Near-ir Illuminationmentioning
confidence: 99%